Plan de negocio para la elaboración y comercialización de salsa picante con zanahoria, en envase importado, en la ciudad de Quito - Serrano Benítez, Jennifer Mikaela (2019)
This business plan is intended to test the feasibility of producing and commercializing a spicy sauce prepared with carrots, in the city of Quito. This product offers its consumers a different alternative to the products that are available in the market nowadays, it brings them the opportunity to eat in a healthier way and provides greater security and complete traceability in their production processes, as well as that of the ingredients that compose it. Thus, PRORGANIC ALIMENTOS is created with the purpose of offering the customer a product adapted to your needs and tastes; and, at the same time, conforms to current trends. Initially, an external and environmental analysis, in which the company operates, is realized to determine a crystal clear and truthful diagnosis, that allows to institute the opportunities as well as the threats to this project. Due to this, actions can be taken on time, to assuage the risks that the company could face. Besides, it is identified and justified the target segment located in the city of Quito, for their propensity to consumption of foods organic, healthy and beneficial in terms of health and welfare. Subsequently, it is carried the qualitative and quantitative client analysis, which allowed to state the characteristics, treatment, presentation and some other aspects that have to qualify the final product. In the same way, and to complement the overall marketing strategy, it was evaluated the price that has to be settled for the company to be competitive and preferred by the client; the best and more convenient channel to get to the final consumer, in terms of promotion as well as in terms of distribution. So a high added value is generated, the product meets and exceeds the expectations of the target segment. Finally, it is built a financial evaluation for the project in a range of projection for five years, reflecting positive and encouraging results, that allows to conclude that the project is feasible with a clear current value of 4.408,82 dollars and an internal rate of return of 13,2 percent.